Gender, language and new literacy - Thüne, Eva-Maria; Leonardi, Simona; Bazzanella, Carla (Continuum, 2006)
Gender, Language and New Literacy presents cross-cultural research on gender as it is lexically and socially categorized in electronic media. For the purposes of the study, the authors have compiled a corpus of gender terms from online thesauruses to show how new technologies interact with gender categorizations in different languages, and how these are related to their respective culture and society. Each language is examined within the same theoretical framework, functional semantics, focusing on lexicon. This common empirical ground facilitates cross-language comparison. The contributors ex.